Analisis Kebutuhan Storybook Etno-ESD Gastronomi Sunda: Fondasi Penguatan Literasi Sains Siswa SD - Windry Syakia; Agnestasia Ramadhani Putri; Srie Mulyati (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The problem addressed in this study stems from the low level of scientific literacy among elementary school students and the suboptimal implementation of Education for Sustainable Development (ESD), which has not been well integrated with local wisdom. In addition, Sundanese gastronomic knowledge is increasingly being eroded by modernization, highlighting the need for innovative, contextual, and meaningful learning media. This study aims to analyze the need for developing a learning medium in the form of a storybook based on Ethno-ESD Sundanese gastronomy as a foundation for strengthening students’ scientific literacy. This study employed a quantitative descriptive method within the Design Based Research (DBR) framework at the needs analysis stage. The sample consisted of fifth-grade elementary school students selected through purposive sampling. Data were collected using a Likert-scale questionnaire covering five aspects: prior learning understanding, learning media needs, scientific literacy, integration of Ethno-ESD, and students’ interest in storybooks. Data were analyzed using descriptive statistics in the form of mean scores. The results indicate that students’ need for developing an Ethno-ESD-based storybook is high, with an average score of 4.13. All aspects fall into high to very high categories, with the highest score in the integration of Ethno-ESD Sundanese gastronomy. These findings suggest that students require contextual and engaging learning media that integrate scientific literacy with daily life and local cultural values. Therefore, the development of an Ethno-ESD-based Sundanese gastronomy storybook has strong potential as an innovative solution to enhance elementary students’ scientific literacy.